Through‐Space Charge Transfer: A New Way to Develop a High‐Performance Fluorescence Sensing Film towards Opto‐Electronically Inert Alkanes - Wang, Zhaolong; Gou, Xinyu; Shi, Qiyuan; Liu, Ke; Chang, Xingmao; Wang, Gang; Xu, Wenjun; Lin, Simin; Liu, Taihong; Fang, Yu (Angewandte Chemie International Edition, 2022)
New strategies are in high demand for fast, sensitive, selective, on‐site and real‐time detection of the important but challenging alkane vapors owing to their opto‐electronic inertness. Herein, we report, for the first time, a high‐performance fluorescent film sensor (FFS) for the alkanes with a rationally designed through‐space charge transfer (TSCT) molecule as the sensing fluorophore. Steady‐state fluorescence, femto‐second transient absorption spectroscopy and theoretical studies revealed continuous TSCT dynamics in the excited U‐shaped molecule with increasing medium polarity. Furthermore, the interlocked, face‐to‐face alignment between the donor and acceptor favors mass transport of the analyte molecules in the film state. As anticipated, the compound‐based FFS showed an experimental detection limit of ≈10 ppm for n‐pentane, less than 5 s for a full detection, negligible interference and super‐stability, revealing the effectiveness of the design strategy. Notably, the sensor is small (≈3.7 cm3), power‐saving, and workable at room temperature. Rational design of an o‐carborane‐based U‐shaped fluorophore possessing through‐space charge transfer (TSCT) properties enables the development of a fluorescence film sensor, which allows high‐performance sensing of opto‐electronically inert alkane vapors. This is ascribed to the microenvironmental sensitivity of the fluorophore and the facilitated mass transfer in the film state.